Explanation is in a file
bit.
ly/3a8Nt8n
Answer:
rdh
Step-by-step explanation:
Answer:
<h2>g( - 3) + 13 = - 2</h2>
Step-by-step explanation:
g(x) = x - 2x²
To find g( - 3) + 13 substitute the value of x that's - 3 into g(x) and add 13 to it
We have
g( - 3) + 13 = - 3 - 2(-3)² + 13
= -- 3 - 2(9) + 13
= 3 - 18 + 13
We have the final answer as
<h3>g( - 3) + 13 = - 2</h3>
Hope this helps you
Your mom smells like poop
Answer:
Step-by-step explanation: the thing is that if kelvin walks 5km south and then 8 km east the displacement is that he won’t really make it to the east.